2013
DOI: 10.1093/mnras/stt1468
|View full text |Cite
|
Sign up to set email alerts
|

AD 775 pulse of cosmogenic radionuclides production as imprint of a Galactic gamma-ray burst

Abstract: We suggest an explanation of a sharp increase in the abundance of cosmogenic radiocarbon found in tree rings dated AD 775. The increase could originate from high-energy irradiation of the atmosphere by a galactic gamma-ray burst. We argue that, unlike a cosmic ray event, a gamma-ray burst does not necessarily result in a substantial increase in long-lived 10 Be atmospheric production. At the same time, the 36 Cl nuclide would be generated in the amounts detectable in the corresponding ice core samples from Gre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 34 publications
0
87
1
Order By: Relevance
“…775 AD was analyzed using biennial 14 C data by Miyake et al (2012), who suggested that the event was probably caused by γ -rays from an unknown nearby supernova. This event is confirmed by annual 14 C data from a German oak tree , Russian and American tree samples (Jull et al 2014), New Zealand trees (Güttler et al 2013), etc., and corals from the Chinese Sea (Liu et al 2014) According to model simulations, the production of 14 C appears in agreement with that of 10 Be Melott and Thomas 2012;Pavlov et al 2013). Although some exotic scenarios were proposed for the event: an unidentified nearby supernova ); a gamma-ray burst (Hambaryan and Neuhäuser 2013;Pavlov et al 2013); or even a cometary impact on Earth (Liu et al 2014), it is generally accepted now that it was a signature of a (probably, consequence of) extreme SEP event Eichler and Mordecai 2012;Usoskin et al 2013;Melott and Thomas 2012;Thomas et al 2013;Cliver et al 2014).…”
Section: The Event Of 775 Ad: the Worst Case Scenario?mentioning
confidence: 82%
“…775 AD was analyzed using biennial 14 C data by Miyake et al (2012), who suggested that the event was probably caused by γ -rays from an unknown nearby supernova. This event is confirmed by annual 14 C data from a German oak tree , Russian and American tree samples (Jull et al 2014), New Zealand trees (Güttler et al 2013), etc., and corals from the Chinese Sea (Liu et al 2014) According to model simulations, the production of 14 C appears in agreement with that of 10 Be Melott and Thomas 2012;Pavlov et al 2013). Although some exotic scenarios were proposed for the event: an unidentified nearby supernova ); a gamma-ray burst (Hambaryan and Neuhäuser 2013;Pavlov et al 2013); or even a cometary impact on Earth (Liu et al 2014), it is generally accepted now that it was a signature of a (probably, consequence of) extreme SEP event Eichler and Mordecai 2012;Usoskin et al 2013;Melott and Thomas 2012;Thomas et al 2013;Cliver et al 2014).…”
Section: The Event Of 775 Ad: the Worst Case Scenario?mentioning
confidence: 82%
“…The non-solar sources include a supernova hidden behind a dust cloud (Allen 2012) and galactic short-duration (Hambaryan & Neuhäuser 2013) and long-duration gamma-ray bursts (Pavlov et al 2013). Melott & Thomas (2012) and Usoskin et al (2013) favor a standard (eruptive flare; Reames 2013) solar source, and Eichler & Mordecai (2012) proposed a non-traditional solar source-a superflare caused by a large comet colliding with the Sun.…”
Section: Introductionmentioning
confidence: 99%
“…The considerations of Cliver et al [11] challenge a suggestion that the 775 event is likely of solar origin. This event could originate from high-energy irradiation of the atmosphere by a Galactic gamma-ray burst [13]. A solar source for the AD 775 event would require the proton fluence F(>30 MeV) = 8 ·10 10 cm −2 , 10 times larger than that of the strongest 3 month interval of SPE activity in the modern era.…”
Section: Discussion: Ultimate Fluxes and Fluencesmentioning
confidence: 99%